Positive Discourse Analysis of Official WeChat Public Accounts of Sports Events from the Perspective of the Attitude System: A Case Study of the Lanzhou Marathon - Wu, Zihan (International Journal of Humanities and Social Science, 2026)
Against the national strategy of mass fitness, official WeChat public accounts have become key channels for sports event communication, yet positive discourse analysis in this field remains insufficient. Based on the attitude system of Appraisal Theory, this paper analyzes attitude resources in original articles from the 2025 Lanzhou Marathon WeChat account using UAM Corpus Tool 6.2. Results show that affect resources dominate, followed by judgment and appreciation. They construct positive discourse via emotional expression, cultural integration and metaphor, enhance emotional resonance and event branding. This study validates the applicability of Appraisal Theory and offers empirical support for interdisciplinary research in sports communication and discourse analysis.